Zwischen logos und icon - Ulrich Engel (Warszawskie Studia Teologiczne)
In his contribution "Zwischen logos und icon. Gegenwartskunst als Anders-Ort der Theologie" (Between logos and icon. Contemporary art as other-place of theology) Ulrich Engel OP examines, starting from the iconic turn, the question what theology (which is primarily committed to the biblical WORD) can learn from IMAGES. Following Foucault's theory of heterotopias (other-places), the study focuses on works of contemporary visual art, which as other-places can expose and make visible hidden, overlooked, misunderstood mechanisms of exclusion. Four artistic positions (Pavel Büchler, Boris Mikhailov, Kris Martin, and Paloma Varga Weisz) are used to show how they cite Christian iconographic traditions and revisit them in a contemporary way. In the omissions and gaps that become apparent in these and structurally similar adaptations, de-emphasizations, and continuations, something appears that is already theologically inherent in the biblical prohibition of images. The Jewish prohibition of images is not an absolute one. For it reminds us that all positively painted images of God always need the theological negative sign, the aesthetic "empty space" in the image itself.